Diagnóstico de la calidad de energía en la planta de procesamiento de Inversiones el Dorado S.A.S. en la ciudad de Duitama (2023)
The work focuses on diagnosing the quality of energy at the processing plant of Inversiones Eldorado SAS in Duitama. The plant is a company dedicated to the production and distribution of meat products, especially chicken meat, with a prominent history in the Boyacá department.